2018
DOI: 10.1097/igc.0000000000001172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-Term Oncological Outcomes Between the Initial Learning Period of Robotic and the Experienced Period of Laparoscopic Radical Hysterectomy for Early-Stage Cervical Cancer

Abstract: Despite RRH being performed by an experienced laparoscopic oncologist, RRH showed inferior long-term oncological outcomes and postoperative complication rates compared with those of LRH during the learning period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…A positive impact on oncological outcome with increased experience has been shown for robotic radical prostatectomy by Galfano et al and was implied by Chong et al, who investigated RRHs during the learning phase compared to conventional laparoscopic radical hysterectomies performed by experienced surgeons. [19,20]. Two recent single-institution studies investigated the impact of learning curve on oncological outcome following RRHs for early stage cervical cancer and found improved survival rates with increased surgical experience, achieving similar levels of adequate experience to our study [14,15].…”
Section: Discussionsupporting
confidence: 71%
“…A positive impact on oncological outcome with increased experience has been shown for robotic radical prostatectomy by Galfano et al and was implied by Chong et al, who investigated RRHs during the learning phase compared to conventional laparoscopic radical hysterectomies performed by experienced surgeons. [19,20]. Two recent single-institution studies investigated the impact of learning curve on oncological outcome following RRHs for early stage cervical cancer and found improved survival rates with increased surgical experience, achieving similar levels of adequate experience to our study [14,15].…”
Section: Discussionsupporting
confidence: 71%
“…From their data on the different parts of robot‐assisted surgery in endometrial cancer, Seamon et al 34 concluded that hysterectomies – and in particular the closure of the vaginal cuff – had the longest learning curve. Other recent studies suggested an impact of the learning curve on oncological outcomes after robot‐assisted radical hysterectomy in women with cervical cancer 35,36 . Chong et al 36 reported inferior OS after robot‐assisted radical hysterectomy during the learning period compared with conventional laparoscopic radical hysterectomy performed by experienced surgeons, though not significant ( P = 0.07).…”
Section: Discussionmentioning
confidence: 93%
“…Other recent studies suggested an impact of the learning curve on oncological outcomes after robot-assisted radical hysterectomy in women with cervical cancer. 35,36 Chong et al 36 reported inferior OS after robot-assisted radical hysterectomy during the learning period compared with conventional laparoscopic radical hysterectomy performed by experienced surgeons, though not significant (P = 0.07). Given the small study size (n = 65) and the absence of a CUSUM analysis, the exact length of the learning curve could not be defined in that study.…”
Section: Discussionmentioning
confidence: 95%
“…To date, there is scarce research on learning curve analysis based on actual survival. Chong et al compared the learning period of robotic (consecutive 65 cases) and skilled period of laparoscopic radical hysterectomy for earlystage cervical cancer [25]. However, the number of learning period cases was not determined according to the learning curve but was randomly included in the consecutive 65 cases.…”
Section: Discussionmentioning
confidence: 99%